Diseminasi dan Adopsi Inovasi Pupuk Bioorganik di Tingkat Petani Kabupaten Lima Puluh Kota - Kurniasih, Dedeh; Warman, Benny; Yulensri, Yulensri; Anidarfi, Anidarfi; Sari, Deliana Andam (Fakultas Pertanian, Universitas Lampung, 2024)
Lima Puluh Kota Region is one of regions in West Sumatra is known for its centers of food crops such as corn, peanuts, sweet potatoes, and paddy. Farmers must be able to optimize the land so that production and productivity of food crop can be increased. The optimization of land in this region can be done by eco-friendly agriculture, such as using bio-organic fertilizer technology. The objective of this research is to identify the rate of dissemination and acceptance of bio-organic fertilizer innovation in Lima Puluh Kota Region Farmers. The research method used a census with the number of respondents are 70 farmers. To describe research variables used descriptive statistical analysis with frequency table. The level of dissemination in this research is measured easy-to-understand information, information relevance, recipients of information. The results of the research are the dissemination rate belongs to the highest category with the score 3.5 and the adoption rate in the higher category with the score 3.5. Keywords: adoption, bio-organic, dissemination, innovation